KEPEMIMPINAN KEPALA DESA DALAM PENINGKATAN PEMBANGUNAN DI DESA RODA KECAMATAN KOLONO KABUPATEN KONAWE SELATAN - Harapik; Wahyuddin; Ulfah Attamimi; Riston G Ahmad (Halu Oleo University, 2025)
This study aims to analyse the role and leadership strategies of the Village Head in enhancing development in Roda Village, Kolono District, South Konawe Regency. Village development is a crucial aspect of improving community welfare, which largely depends on the quality of leadership at the local level. This research uses a qualitative approach with a descriptive method, employing in-depth interviews, observation, and document analysis. The findings indicate that the Village Head of Roda plays a central role in designing development programs, mobilising community participation, and establishing coordination with external parties, such as regional governments and private institutions. Communicative, participatory, and responsive leadership has become a key factor in the success of various development programs, including road infrastructure, healthcare facilities, and community economic empowerment. These findings highlight the importance of adaptive and visionary village leadership in promoting sustainable local development.